University students’ health-related quality of life and its determinants. Results from a cross-sectional survey during the COVID-19 pandemic - Karoline Wagner; Zoë Reinhardt; Sarah Negash; Lena Weber; Andreas Wienke; Rafael Mikolajczyk; Amand Führer (PLoS ONE, 2025)
Being a university student is a vulnerable period marked by transitions and uncertainties which can impair their physical and mental well-being as well as overall quality of life. The existing literature suggests that certain groups of students might be particularly affected by that. In addition, quality of life might have been further affected by the COVID-19 pandemic. Therefore, this article investigated university students’ quality of life and its determinants during the COVID-19 pandemic using an online survey among students of one German university. Quality of life was measured using SF-12’s physical (PCS) and mental dimension (MCS). We conducted stratified descriptive analyses followed by regression analyses. 875 respondents completed the questionnaire, of whom 63.0% were female and 95.7% had a German nationality and 16.0% reported having a migration background. Mean age was 23 years. Medical (17.7%) and law students (15.8%) were the biggest groups, but all other faculties of the university were also covered. Concerning respondents’ health-related quality of life, mean PCS was 51 (95%CI = (47–55)), while mean MCS was 36 (95%CI = (30–43). Students with non-German nationality (PCS: 49; MCS: 29) and students with migration background (PCS: 50; MCS: 31) showed particularly low quality of life in the mental dimension. In multivariable regression analyses, associations of the included determinants with PCS were rather weak. In contrast, there were strong associations between MCS and having a migration background with regression coefficient β = -26.1 (95%CI = (-38.5 – -13.7)) and studying Law with β = -17.7 (95%CI = (-28.2 – -7.2)). When comparing these findings with pre-pandemic studies, it seems that university students’ quality of life during the pandemic was as low as it had been before while–as in pre-pandemic studies–certain groups of students generally fared worse than others did. This suggests that universities should actively promote students’ health and should implement measures to specifically support particularly vulnerable students such as students with migration background or students of certain subjects.